2020
DOI: 10.1038/s41598-020-75751-w
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal miRNAs regulated in response to dietary lipids

Abstract: The role of miRNAs in intestinal lipid metabolism is poorly described. The small intestine is constantly exposed to high amounts of dietary lipids, and it is under conditions of stress that the functions of miRNAs become especially pronounced. Approaches consisting in either a chronic exposure to cholesterol and triglyceride rich diets (for several days or weeks) or an acute lipid challenge were employed in the search for intestinal miRNAs with a potential role in lipid metabolism regulation. According to our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
3
5
0
Order By: Relevance
“…13 In this study, vegetable lipids were the nutrients associated with the highest number of stool DEmiRNAs, together with animal lipids (namely miR-425-3p, miR-638, miR-8063 and miR-4277), but the latter showed an opposite trend. This result is consistent with previous evidence on the activity of lipids in modulating miRNA expression in different tissues, including gut, 77 adipocytes, 78 and plasma. 79 A functional enrichment analysis was performed to identify the candidate downstream signalling and metabolic pathways that may be affected by an intestinal miRNA expression modulation, which is reflected in stool samples.…”
Section: Discussionsupporting
confidence: 93%
“…13 In this study, vegetable lipids were the nutrients associated with the highest number of stool DEmiRNAs, together with animal lipids (namely miR-425-3p, miR-638, miR-8063 and miR-4277), but the latter showed an opposite trend. This result is consistent with previous evidence on the activity of lipids in modulating miRNA expression in different tissues, including gut, 77 adipocytes, 78 and plasma. 79 A functional enrichment analysis was performed to identify the candidate downstream signalling and metabolic pathways that may be affected by an intestinal miRNA expression modulation, which is reflected in stool samples.…”
Section: Discussionsupporting
confidence: 93%
“…Some miRNAs appear to do this by affecting lipid metabolism in the small intestine. It has been shown, for instance, that mice with a small intestinal DICER-knock out display abnormal absorption and processing of lipids [ 31 , 32 ]. Lipid metabolism is also important in the maintenance of the regenerative capacity of the small intestinal crypt [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small intestinal miRNA expression is significantly altered by high fat diet and excessive lipid exposure 43 , 44 . Furthermore, a study utilizing a mouse model of intestinal Dicer-1 knockout showed that disruption of intestinal miRNA expression results in changes to lipid absorption and accumulation 45 . Other studies have confirmed extensive regulation of lipid metabolism by intestinal miRNAs 46 .…”
Section: Discussionmentioning
confidence: 99%